2018
DOI: 10.1177/1010428318757103
|View full text |Cite
|
Sign up to set email alerts
|

HE4 is superior to CA125 in the detection of recurrent disease in high-risk endometrial cancer patients

Abstract: Elevated serum HE4 is an independent risk factor for reduced disease-free survival and overall survival. HE4 seems to be superior to CA125 in the detection of recurrent disease during follow-up, mainly in high-risk endometrial cancer patients who are more prone to distant metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 41 publications
9
74
1
Order By: Relevance
“…There is no specific blood protein biomarker that is recommended for use following an EC diagnosis; instead, regular clinical examination is advised with imaging. The ovarian cancer markers CA125 and HE4 have been shown to significantly correlate with prognosis; however, their detection rates in metastatic disease are low-54% and 75% respectively-and even lower with local recurrence: 39% and 16% [5]. Hence, more effective biomarkers are required that can detect EC recurrence and disease progression earlier, as well as reliably reflecting the underlying kinetics of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…There is no specific blood protein biomarker that is recommended for use following an EC diagnosis; instead, regular clinical examination is advised with imaging. The ovarian cancer markers CA125 and HE4 have been shown to significantly correlate with prognosis; however, their detection rates in metastatic disease are low-54% and 75% respectively-and even lower with local recurrence: 39% and 16% [5]. Hence, more effective biomarkers are required that can detect EC recurrence and disease progression earlier, as well as reliably reflecting the underlying kinetics of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Abbink et al . [15] reported the usefulness of HE4 protein concentration assay in detecting distant metastatic foci in cases of endometrial cancer, when its concentration is significantly higher than during local recurrence. In this function it performs significantly better than CA125, which was found elevated only in 37% of patients, compared to 67% for HE4.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, studies reporting significant differences in HE4 values when analyzing other prognostic factors, such as deep myometrial invasion, did not find this correlation when studying lymphatic involvement . One study suggested that the discrepancy in correlation with lymph node metastasis might be due to the small number of cases .…”
Section: Summary Of Findingsmentioning
confidence: 95%
“…Existing evidence on the application of HE4 to detect lymphatic metastases is conflicting. Some studies have found no significant difference between preoperative HE4 level and lymphatic metastasis, whereas others have reported a significant rise in preoperative HE4 if lymphatic involvement is present …”
Section: Summary Of Findingsmentioning
confidence: 96%